Longitudinal population subgroups of CRP and risk of depression in the ALSPAC birth cohort - Osimo, Emanuele F; Stochl, Jan; Zammit, Stan; Lewis, Glyn; Jones, Peter B; Khandaker, Golam M (Comprehensive psychiatry, 2020)
BACKGROUND: Meta-analyses confirm increased circulating C-reactive protein (CRP) levels in depression. Longitudinal studies have linked one-off measurements of CRP at baseline with increased risk of developing depressive symptoms subsequently at follow-up, but studies with repeat CRP measures from the same individuals are scarce. METHODS: We have examined whether longitudinal patterns of inflammation, based on three CRP measurements from childhood to early-adulthood, are associated with the risk of depression in early-adulthood in the Avon Longitudinal Study of Parents and Children, a prospective birth cohort. RESULTS: Using Gaussian mixture modelling of available CRP data from age 9, 15 and 18 years, we identified four population clusters/sub-groups reflecting different longitudinal patterns of CRP: persistently low (N=463, 29.5%); persistently high (N=371, 24%); decreasing (N=360, 23%); increasing (N=367, 23.5%). The increasing group showed a steep increase in CRP levels between adolescence and early-adulthood. Participants in this group had a higher risk of moderate/severe depression at age 18 years, compared with those with persistently low CRP; adjusted odds ratio (OR)=3.78 (95% Confidence Interval (CI), 1.46-9.81; p=0.006). The odds of moderate/severe depression were also increased for the persistently high CRP group, but this was not statistically significant; OR=2.54 (95% CI, 0.90-7.16). LIMITATIONS: Repeat CRP measures were available for a subset, who may not be representative of all cohort participants. CONCLUSIONS: The results suggest that an increasing pattern of inflammation from adolescence to early-adulthood is associated with risk of depression in early-adulthood.
Keywords: Male; kohortové studie; longitudinální studie; Inflammation; Cohort Studies; Adolescent; Child; dítě; Adult; ALSPAC; C-reaktivní protein; Prospective Studies; dospělí; mužské pohlaví; deprese; depresivní poruchy; mladiství; lidé; ženské pohlaví; C-reactive protein; Humans; Risk; Longitudinal Studies; C-Reactive Protein; Female; riziko; Depression; Depressive Disorder; CRP; Immunopsychiatry; prospektivní studie